Imagery and Figurative Language in Emily Dickinson’s Poems - Kusumaningrum, Dyah Arindi (English Journal Antartika, 2023)
Abstract – This study examines the types of imagery and figurative language used in several Emily Dickinsonpoems. This research uses a qualitative descriptive method to analyze the study of imagery and figurativelanguage in poems. Data were taken from seven poems, namely Because I Could Not Stop for Death, WildNights, With a Flower, I Died for Beauty, I Never Saw a Moor, I Heard Fly Buzz When I Die, and I'm Nobody!Who You? then divided into several types of imagery and figurative language. The results of this study indicatethat: (1) Three types of imagery are found in poems, namely visual imagery, tactile imagery, and auditoryimagery. There are fifty nine imagery data, which includes fifty visual imagery data, one tactile imagery data,and eight auditory imagery data. (2) There are three types of figurative language in poems, namelypersonification, metaphor, and simile. With a total of nine figurative language data, which includes sixpersonification data, two metaphor data, and one simile data. (3) Then it was found that the implied meanings inthe figurative language and imagery Emily Dickinson's poems are about death, relationship, feminine beauty,life, and faith.